2019
DOI: 10.1111/rda.13432
|View full text |Cite
|
Sign up to set email alerts
|

The impact of phytoestrogen source supplementation on reproductive performance, plasma profile, yolk fatty acids and antioxidative status in aged laying hens

Abstract: Contents The objectives of this study were to investigate the effects of flaxseeds and/or fenugreek seeds as a source of phytoestrogens in laying feed on productive performance, egg quality, yolk fatty acids, plasma profile and antioxidative status in aged laying hens. A total of 120 Bovans Brown hens at 65 weeks of age were housed individually in laying cages in an open‐sided building under a 16‐hr light: 8‐hr dark lighting schedule. Hens were randomly divided into four experimental treatments (n = 30 each): … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 35 publications
8
47
0
3
Order By: Relevance
“…Similar results were also reported by Zhang et al ., who found that broiler breast muscle MDA content was increased and T‐SOD activity was decreased by transport stress. Various studies have demonstrated that the addition of feed additives to diets had positive effects on the antioxidative capacity of chickens . Saleh et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were also reported by Zhang et al ., who found that broiler breast muscle MDA content was increased and T‐SOD activity was decreased by transport stress. Various studies have demonstrated that the addition of feed additives to diets had positive effects on the antioxidative capacity of chickens . Saleh et al .…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated that the addition of feed additives to diets had positive effects on the antioxidative capacity of chickens. 10,11,42,43 Saleh et al 42 reported that dietary phytogenics supplementation could improve the antioxidative status and humoral immunity of broilers. Zhang et al 10,11 reported that dietary resveratrol and L-theanine supplementation could attenuate breast muscle oxidative injury induced by transport stress in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the current findings, Safaa (2007) reported that fenugreek did not have a significant effect on egg production, egg weight and egg mass. In contrast, with Saleh et al (2019) indicated that hen day egg production and egg mass were significantly increased by dietary supplementation of fenugreek. Park et al (2012) reported that supplementation of turmeric at 0.1 ,0.25 and 1.0% did not influence of egg on old leghorn laying hens.…”
Section: -Egg Mass G / Henmentioning
confidence: 87%
“…Generally, the distinguishing group among all the treatments in the number of eggs and laying rate% was the one that groups fed on diet with mixture of TU 0.1 + FE 0.2 % .There are conflicting results regarding the effect of adding fenugreek or turmeric to laying hens diet on the egg production rate. In this respect, Saleh et al (2019) mentioned that hen day egg production was significantly increased by dietary supplementation of fenugreek. Awadein et al (2010) reported increased egg production rate and related to fenugreek seeds dietary supplementation at 0.01 to 0.5% levels.…”
Section: -Laying Rate: Data Inmentioning
confidence: 99%
See 1 more Smart Citation